MicroRNA-185-5p mediates regulation of SREBP2 expression by hepatitis C virus core protein - Li, Min (World J Gastroenterol, 2015)
AIM: To investigate the molecular mechanism for regulation of cholesterol metabolism by hepatitis C virus (HCV) core protein in HepG2 cells. METHODS: HCV genotype 1b core protein was cloned and expressed in HepG2 cells. The cholesterol content was determined after transfection. The expression of sterol regulatory element binding protein 2 (SREBP2) and the rate-limiting enzyme in cholesterol synthesis (HMGCR) was measured by quantitative real-time PCR and immunoblotting after transfection. The effects of core protein on the SREBP2 promoter and 3’-untranslated region were analyzed by luciferase assay. We used different target predictive algorithms, microRNA (miRNA) mimics/inhibitors, and site-directed mutation to identify a putative target of a particular miRNA. RESULTS: HCV core protein expression in HepG2 cells increased the total intracellular cholesterol level (4.05 ± 0.17 vs 6.47 ± 0.68, P = 0.001), and this increase corresponded to an increase in SREBP2 and HMGCR mRNA levels (P = 0.009 and 0.037, respectively) and protein expression. The molecular mechanism study revealed that the HCV core protein increased the expression of SREBP2 by enhancing its promoter activity (P = 0.004). In addition, miR-185-5p expression was tightly regulated by the HCV core protein (P = 0.041). Moreover, overexpression of miR-185-5p repressed the SREBP2 mRNA level (P = 0.022) and protein expression. In contrast, inhibition of miR-185-5p caused upregulation of SREBP2 protein expression. miR-185-5p was involved in the regulation of SREBP2 expression by HCV core protein. CONCLUSION: HCV core protein disturbs the cholesterol homeostasis in HepG2 cells via the SREBP2 pathway; miR-185-5p is involved in the regulation of SREBP2 by the core protein.